REVIEW OF THE INTERNET BLOCKING CASE IN PAPUA IN CYBER LAW PERSPECTIVE - Melvin Elvino Putra (Faculty of Law Universitas Lampung, 2022)
The internet has become an essential part of modern life, increasing the efficiency of everything. It should be no surprise that internet abuse can lead to crimes that harm everyone. As a result, there is a need for legal safeguards known as Cyber Law, which intersects with Human Rights. The case of internet blocking in Papua, in which the government blocked or slowed internet connections in Papua, is the subject of this article because it raises many issues in the fields of Human Rights and Cyber Law, which, on the human rights side, is regulated in the 1945 Constitution, which states that everyone has the right to benefit from technology. In this case, the government cannot meet the aspect of Human Rights. However, in Cyber Law, this is intended as a limitation to reduce a crime on social media or the internet that causes chaos. As a result, this paper will elaborate on the Papua case from the standpoint of Cyber Law. The Administrative Court's decision used a normative legal approach and an objective case approach to investigate this phenomenon experimentally. The study then employs a qualitative method with literature and empirical approach, obtaining data through legal analysis and social phenomena that occur in society. Although further investigations are needed, the present study contributes to a better understanding of the case that occurred in Papua related to the government's blocking or disconnection of the internet. It was not a violation of the law because the government at the time made good decisions for the entire community's benefit, ensuring that everyone was safe from cybercrime or false news, which has the potential to sever Indonesia's unity.